Characteristics of Colorectal Cancer that Produce Positive Immunochemical Occult Blood Test Results on Stool Obtained by Digital Rectal Examination - Hidenori Nakama; Bing Zhang; ASM Abdul Fattah; Noboru Kamijo; Xing Zhang (Canadian Journal of Gastroenterology)
OBEJCTIVE: To clarify the clinicopathological features of colorectal cancer that show positive results on an immunochemical fecal occult blood test of stool obtained by digital rectal examination.